A Scenario of Poisoning in Children in Manipal Teaching Hospital - Malla, Tejesh; Malla, Kalpana K; Rao, KS; Gauchan, Eva; Basnet, Sahisnuta; Koirala, DP (Journal of Nepal Paediatric Society, 2011)
Objective: To see the pattern and prevalence of poisoning in children in Manipal Teaching Hospital, Pokhara. The cases were also considered in relevance to the age groups with various agents, the commonly observed clinical features in various poisonings and mortality. Study design: Hospital based retrospective study. Study period: 4 years (January 2006 – January 2010). Study place: Department of Paediatric, Manipal Teaching Hospital, Pokhara. Material and Methods: A detailed study of all the case files of the children admitted with various acute poisonings, where the causative agent was known, was done. Results: A total number of 94 children (56 males & 38 females) were admitted with poisoning (1.79% of the total admissions) during that period. Maximum number of children were of the preschool age group i.e. < 5 years (64.89%). Organophosphorus Compounds (OPC) (27%) and Kerosene Oil (23%) were the two most frequent agents involved. The other agents included Snake bite (19%), Drugs/ Chemicals (16%), Dhatura (12%), and Mushroom poisoning (3%). The most common nature of poisoning noted was accidental (95%). The mortality rate observed was 6.38%. Conclusion: OPC and Kerosene Oil poisoning were the two most common poisoning observed in this study comprising almost half the cases; accidental poisoning was the most common pattern noted and there was a male predominance. Early recognition and timely treatment can decrease the mortality. Key words: Poisoning; Organophosphorus and Kerosene poisoning; Snake bite. DOI: 10.3126/jnps.v31i2.3634 J Nep Paedtr Soc 2010;31(2):83-88